WSN sensor node placement approach using Territorial Predator Scent Marking Algorithm (TPSMA) - Abidin H.Z.; Din N.M. (IEEE Computer Society, 2023)
Optimum sensor node placement for Wireless Sensor Network (WSN) is needed for cost effective deployment that provides maximum coverage and minimum energy consumption without jeopardizing the connectivity. A sensor node placement technique that utilizes a new biologically inspired optimization technique that imitates the behavior of territorial predators in marking their territories with their odours known as Territorial Predator Scent Marking Algorithm (TPSMA) is proposed in this paper. The TPSMA deployed in this paper uses the minimum uncovered area as the objective function. The performance of the proposed technique is then compared with other two sensor node placement schemes that are based on Integer Linear Programming (ILP) in terms of coverage ratio, connectivity and energy consumption. Simulation results show that the WSN deployed with the proposed sensor node placement scheme outperforms the other two schemes with larger coverage ratio, full connectivity and lower energy consumption. 2013 IEEE.